Inland recreational fisheries contribute nutritional benefits and economic value but are vulnerable to climate change - Lynch, Abigail J; Embke, Holly S; Nyboer, Elizabeth A; Wood, Louisa E; Thorpe, Andy; Phang, Sui C; Viana, Daniel F; Golden, Christopher D; Milardi, Marco; Arlinghaus, Robert; Baigun, Claudio; Beard, T Douglas; et al. (Nature food, 2024)
Inland recreational fishing is primarily considered a leisure-driven activity in freshwaters, yet its harvest can contribute to food systems. Here we estimate that the harvest from inland recreational fishing equates to just over one-tenth of all reported inland fisheries catch globally. The estimated total consumptive use value of inland recreational fish destined for human consumption may reach US$9.95 billion annually. We identify Austria, Canada, Germany and Slovakia as countries above the third quantile for nutrition, economic value and climate vulnerability. These results have important implications for populations dependent on inland recreational fishing for food. Our findings can inform climate adaptation planning for inland recreational fisheries, particularly those not currently managed as food fisheries.
Keywords: nutriční hodnota; zachování přírodních zdrojů; Germany; sladká voda; Canada; zvířata; Fishes; ryby; Animals; lidé; Nutritive Value; Recreation; Conservation of Natural Resources; Slovenská republika; rybářství; Climate Change; Kanada; Fresh Water; rekreace; klimatické změny; Rakousko; Humans; Německo; Austria; Slovakia; Fisheries